2016
DOI: 10.1038/cgt.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between RIZ1 gene therapy and paclitaxel in SiHa cervical cancer cells

Abstract: RIZ1 is a tumor suppressor gene. The purpose of the present study was to investigate the inhibitory effect of RIZ1 gene therapy on the growth of SiHa cervical cancer cells and its synergism with paclitaxel. The expression levels of RIZ1 were examined by real-time PCR and western blotting before and after transfection of RIZ1. The effects of paclitaxel or pcDNA3.1(+)-RIZ1 alone or in combination, on the proliferation of SiHa cells were evaluated by MTT method. The inhibitory effect on the proliferation of SiHa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Paclitaxel (Figure 1) is widely known to specifically interact with tubulins and is one of the first line treatments for ovarian and breast cancer [40,41]. In this context, we used Paclitaxel as a standard and found that it affected HeLa and CaSki at a concentration of 0.19 μM at 48 h of exposure.…”
Section: Resultsmentioning
confidence: 98%
“…Paclitaxel (Figure 1) is widely known to specifically interact with tubulins and is one of the first line treatments for ovarian and breast cancer [40,41]. In this context, we used Paclitaxel as a standard and found that it affected HeLa and CaSki at a concentration of 0.19 μM at 48 h of exposure.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the use of only the C33a cell line-which is negative for HPV DNA and RNA-as an experimental model is not enough and cannot be considered a representative study sample, taking into account the cellular Another tumor suppressor gene studied in cervical cancer is retinoblastoma protein zinc finger gene (RIZ), specifically its RIZ1 expression products, which can induce cell cycle arrest and apoptosis. Cheng et al found the upregulation of RIZ1 in SiHa(HPV16+ve) cells reduced cell proliferation, and treatment with PTX increased the expression level of RIZ1 and enhanced tumor suppressive function, indicating that RIZ1 combined with PTX has a synergic effect [40]. The same group also found that RIZ1 overexpression combined with RT achieved an increased apoptosis rate and DNA damage in HeLa and SiHa cells, with an enhanced radiosensitivity of cancer cells [41].…”
Section: Tumor Suppressor Gene Restorationmentioning
confidence: 98%
“…Another tumour suppressor gene with clinical importance in cervical cancer gene therapy is the retinoblastoma protein zinc finger gene 1 (RIZ1) since it can induce apoptosis and cell cycle arrest. Cheng et al demonstrated that overexpression of RIZ1 expression in HPV16-positive cervical cancer cells could lead to impaired cell proliferation and increased apoptosis [131]. When this overexpression is combined with radiotherapy, it leads to increased apoptosis and DNA damage in HeLa and SiHa cells [146].…”
Section: Plasmidsmentioning
confidence: 99%